A GREEN AND LOW-COST OF MESOPOROUS ELECTRODE BASED ACTIVATED CARBON MONOLITH DERIVED FROM FALLEN TEAK LEAVES FOR HIGH ELECTROCHEMICAL PERFORMANCE - Taer, Erman; Mardiah, Miftah Ainul; Agustino, Agustino; Mustika, Widya Sinta; Apriwandi, Apriwandi; Taslim, Rika (Journal of Applied Engineering Science, 2021)
Mesoporous carbon materials derived from the novel biomass of fallen teak leaves were synthesized using versatile, low cost, and environmentally friendly route. Therefore, mesoporous carbon materials were prepared in the monolith form, followed by treatment with the integrated pyrolysis of both carbonization and physical activation. In addition, there are detailed studies and analysis on the influences of chemical activation processes under different concentrations on the textural properties, morphology, crystalline degree, surface element and electrochemical performance. These mesoporous carbon possess the highest specific surface area of 489.81 m2 g-1, with a pore volume of 0.293 cm3 g-1, and well-developed mesoporosity. Hence, the electrode of mesoporous carbon for supercapacitor in a two electrode system with 1 M H2SO4, exhibits a high specific capacitance 280 F g-1 without heteroatom doping. This report provides an effective route to utilize the novel biomass of fallen teak leaves, with the potential benefits of waste reduction and the production of excellent electrode to serve as energy storage materials.